Cocoa: Driver of Deforestation in the Democratic Republic of the Congo? - Beule, H. de; Jassogne, Laurence T.P.; Asten, Piet J.A. van (2014)
The Democratic Republic of the Congo (DRC) accounts for the largest part of the Congo Basin forest: two-thirds (some 155 million hectares) are forested and 69 percent of which is dense humid forest. With a surge in world market commodity prices for cocoa in 2008 and a steady 2-5% annual increase in global demand, incentives to expand cocoa production are significant. This study determines the role of cocoa in the RDC in terms of current deforestation, identifies actors, and estimates future expansion. Although cocoa in occurs in eight regions in the DRC, authors focused on the four major growing regions in this study, using a rough estimation to get an “order of magnitude” of cocoa as a driver of deforestation. The authors found that cocoa expansion could lead to the loss of 176-395 square kilometres of forest in the next decade, strongest in the Mambasa region and in Equatorial Province surrounding Mbandaka, Bikoro and Lukolela. However, migration of internally displaced people, production of food crops, and illegal logging are likely more severe drivers of deforestation in the Mambasa region. Deforestation caused by cocoa growing in Equatorial Province will largely depend on rejuvenation of existing fields.